Sex-based associations with microvascular injury and outcomes after ST-segment elevation myocardial infarction - Mark C Petrie; Naveed Sattar; Colin Berry; Kenneth Mangion; Annette Marie Maznyczka; David Carrick; Jaclyn Carberry; Margaret McEntegart; Hany Eteiba; Mitchell Lindsay; Stuart Hood; Stuart Watkins; et al. (Open Heart)
Objectives We aimed to assess for sex differences in invasive parameters of acute microvascular reperfusion injury and infarct characteristics on cardiac MRI after ST-segment elevation myocardial infarction (STEMI).Methods Patients with STEMI undergoing emergency percutaneous coronary intervention (PCI) were prospectively enrolled. Index of microcirculatory resistance (IMR) and coronary flow reserve (CFR) were measured in the culprit artery post-PCI. Contrast-enhanced MRI was used to assess infarct characteristics, microvascular obstruction and myocardial haemorrhage, 2 days and 6 months post-STEMI. Prespecified outcomes were as follows: (i) all-cause death/first heart failure hospitalisation and (ii) cardiac death/non-fatal myocardial infarction/urgent coronary revascularisation (major adverse cardiovascular event, MACE) during 5- year median follow-up.Results In 324 patients with STEMI (87 women, mean age: 61 ± 12.19 years; 237 men, mean age: 59 ± 11.17 years), women had anterior STEMI less often, fewer prescriptions of beta-blockers at discharge and higher baseline N-terminal pro-B-type natriuretic peptide levels (all p < 0.05). Following emergency PCI, fewer women than men had Thrombolysis in Myocardial Infarction (TIMI) myocardial perfusion grades ≤ 1 (20% vs 32%, p = 0.027) and women had lower corrected TIMI frame counts (12.94 vs 17.65, p = 0.003). However, IMR, CFR, microvascular obstruction, myocardial haemorrhage, infarct size, myocardial salvage index, left ventricular remodelling and ejection fraction did not differ significantly between sexes. Female sex was not associated with MACE or all-cause death/first heart failure hospitalisation.Conclusion There were no sex differences in microvascular pathology in patients with acute STEMI. Women had less anterior infarcts than men, and beta-blocker therapy at discharge was prescribed less often in women.Trial registration number NCT02072850.